A Case Report VP shunt in Non Communicating Hydrocephalus due to Intracerebral Hemorrhage - Firman Muharam; Rully Hanafi Dahlan; Seyline Estethia Ompusunggu (Sumatera Medical Journal, 2022)
Stroke is one of the top three cause of death and disability globally. Approximately, only 10% to 15% of first-ever stroke are intracerebral hemorrhages (ICHs), but the rates of disability and death are significantly higher. Hydrocephalus may occur in more than 50% of patients with intraventricular hemorrhage (IVH), which is secondary to ICH. Intraventricular hemorrhage (IVH), an accumulation of blood to ventricles that may be cause by extension of ICH, occurs in up to 50% of patients with primary ICH. Hydrocephalus itself may serves as a predictor of poor outcome after ICH.1,2,3 A 71 years old male came to the hospital with the complaint of loss of consciousness, difficulty in communicating, and weakness of extremities on the left side of the body since 12 hours ago. The complaint was preceded by headache that did not alleviate with medication since 1 day before admission and there was history of slurred speech. A head CT scan without contrast was done and the result showed an intracerebral hemorrhage and a suggestive obstructive hydrocephalus. The patient was diagnosed noncommunicating hydrocephalus due to spontaneous intracerebral haemorrhage (ICH) at the right thalamus with intraventricular haemorrhage due to suspect hypertension with differential diagnosis of cerebral amyloid angiopathy with emergency hypertension. The patient was advised to underwent an emergency VP shunt placement. Implantation of a ventriculoperitoneal (VP) shunt is the most widely used treatment of hydrocephalus. Considered to be a major privonce of neurosurgery, it accounts for 70.000 hospital admission in the US. Even though, VP shunting of CSF reduces the morbidity and mortality of post-hemorrhagic. hydrocephalus, it is associated with potential complications requiring multiple surgical procedures, as well as shunt revision due to its failure during the patient’s lifetime.4